2023
DOI: 10.1093/cid/ciad106
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination Uptake and Associated Factors Among Adults With and Without Human Immunodeficiency Virus in a Large, Integrated Healthcare System

Abstract: Background Influenza vaccination is recommended for adults regardless of HIV status. There may be facilitators or barriers to vaccinating people with HIV (PWH) that differ from people without HIV (PWoH). We sought to describe the uptake of influenza vaccination by HIV status and identify factors associated with vaccination. Methods We abstracted data from the electronic health records of PWH and PWoH in Kaiser Permanente Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In this study, the vaccination rates for HBV and pneumococcus increased annually, which is encouraging, whereas the influenza vaccination rate remained low despite the recommendations for high-priority annual immunization. A study conducted in the US showed that the influenza vaccination rate was almost 50.0% higher among people with HIV than among those without HIV, reflecting greater engagement with the healthcare system [ 14 ]. Therefore, integrated care may play a role in improving vaccination rates in this population.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the vaccination rates for HBV and pneumococcus increased annually, which is encouraging, whereas the influenza vaccination rate remained low despite the recommendations for high-priority annual immunization. A study conducted in the US showed that the influenza vaccination rate was almost 50.0% higher among people with HIV than among those without HIV, reflecting greater engagement with the healthcare system [ 14 ]. Therefore, integrated care may play a role in improving vaccination rates in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Data on other vaccinations among PLHIV are limited but suggest receipt of other vaccines, such as the human papillomavirus (HPV) vaccine, which is recommended to be administered post partum, is similarly low . Influenza vaccination rates for the general population of people living with HIV is also suboptimal, with data from a large health system in California from 2013 to 2018 revealing influenza vaccination uptake at 65% to 69% for PLHIV . Given the paucity of data on the topic of routine vaccination in PLHIV, our objective was to estimate the prevalence of and identify factors associated with receiving influenza and/or Tdap vaccinations among pregnant PLHIV participating in a large multisite prospective cohort in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…24 Influenza vaccination rates for the general population of people living with HIV is also suboptimal, with data from a large health system in California from 2013 to 2018 revealing influenza vaccination uptake at 65% to 69% for PLHIV. 25 Given the paucity of data on the topic of routine vaccination in PLHIV, our objective was to estimate the prevalence of and identify factors associated with receiving influenza and/or Tdap vaccinations among pregnant PLHIV participating in a large multisite prospective cohort in the United States. The study population for this analysis was derived from participants in the WHS (Figure).…”
Section: Introductionmentioning
confidence: 99%